2020
DOI: 10.3389/fpubh.2020.00055
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Carriage of Vancomycin-Resistant Enterococci and Carbapenem-Resistant Gram-Negative Bacteria in an Endemic Setting: Prevalence, Risk Factors, and Outcomes

Abstract: Background: Gastrointestinal carriage of vancomycin-resistant enterococci (VRE) and carbapenem-resistant Gram-negative bacteria (CRGN) constitutes a major public health concern as it may be followed by clinical infection development or lead to intra-hospital dissemination. Detection of carriers and implementation of infection control measures are essential in every hospital. In this study we determined the point prevalence of VRE and CRGN in the fecal flora of the inpatients of a tertiary university hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Enteric pathogens, which must also be investigated in asymptomatic subjects, should be detected with conventional methods (culture, microscopy, or antigen test) and/or with molecular diagnosis (PCR-based panels) that have shown a high specificity and sensitivity compared to conventional methods in rapid detection of pathogens [ 60 ]. Furthermore, it is mandatory to test all fecal samples for antibiotic-resistant bacteria (including meticillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococci (VRE), extended-spectrum β-lactamase-producing Enterobacteriaceae, and carbapenem-resistant Enterobacteriaceae/carbapenemase-producing Enterobacteriaceae), considering the burden of the gastrointestinal carriage in asymptomatic subjects [ 61 , 62 ] and the reporting of some serious adverse events associated to sepsis after FMT [ 13 ]. Nowadays, due to the emerging Covid-19 pandemic, a panel of international experts has suggested to include in the tests for Sars-CoV-2 a thorough nasopharyngeal swab and/or RNA detection in stool [ 63 ].…”
Section: Selection and Screening Of Stool Donorsmentioning
confidence: 99%
“…Enteric pathogens, which must also be investigated in asymptomatic subjects, should be detected with conventional methods (culture, microscopy, or antigen test) and/or with molecular diagnosis (PCR-based panels) that have shown a high specificity and sensitivity compared to conventional methods in rapid detection of pathogens [ 60 ]. Furthermore, it is mandatory to test all fecal samples for antibiotic-resistant bacteria (including meticillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococci (VRE), extended-spectrum β-lactamase-producing Enterobacteriaceae, and carbapenem-resistant Enterobacteriaceae/carbapenemase-producing Enterobacteriaceae), considering the burden of the gastrointestinal carriage in asymptomatic subjects [ 61 , 62 ] and the reporting of some serious adverse events associated to sepsis after FMT [ 13 ]. Nowadays, due to the emerging Covid-19 pandemic, a panel of international experts has suggested to include in the tests for Sars-CoV-2 a thorough nasopharyngeal swab and/or RNA detection in stool [ 63 ].…”
Section: Selection and Screening Of Stool Donorsmentioning
confidence: 99%
“…The selection of appropriate antibiotics based on bacterial resistance patterns is important for the assessment of bacterial resistance factors and controlling the incidence of resistance from bacteria in animal food to humans (Putra et al 2019;Vasilakopoulou et al 2020). Aztreonam, Gentamicin, Chloramphenicol, Tetracycline, and Ciprofloxacin are broad-spectrum antibiotics from several classes of effective antibiotics and are often used in cases of E. coli bacterial infections (Karaman 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is in accordance with these findings. However, some studies reported a low level of CRO, even up to 0.5% [ 3 , 11 , 12 ]. The markedly high degree of resistance of gut colonizers to carbapenem in this study can be attributed to geographical variation, different profiles of antibiotic consumption, and the difference in the predominance of bacteria isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the use of invasive devices, three or more classes of antibiotics, hospitalization during the previous six months, comorbidities, and hospital stay for ≥48 h were significantly associated with the development of CRO carriage [ 5 , 9 , 11 , 12 ]. While the use of multiple antibiotics causes selection pressure, invasive devices, and comorbid conditions lead to prolonged hospitalization resulting in the gastrointestinal carriage of CRO [ 11 , 12 ]. Though some studies reported the age of patients as being a risk factor, we did not find this result [ 5 ].…”
Section: Discussionmentioning
confidence: 99%